Matrix metalloproteinases in cancer biology: a review - Nabeel, Ibrahim Wisam; Abdull Rasad, Mohammad Syaiful Bahari; Doolaanea, Abd Almonem (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Matrix metalloproteinases (MMPs) are a group of proteinases that are involved with the enzymatic breakdown of the extracellular matrix and basement membrane components. These enzymes are important in regulating vital physiological functions such as embryonic development, wound healing and tissue remodelling. However, several disorders may result from the exaggerated function of these enzymes such as ulcers, rheumatoid arthritis and invasive tumours. In tumours, the effect of these enzymes is not limited to invasion as it was traditionally believed but it also extends to the other oncogenic hallmark processes such as proliferation, angiogenesis, epithelial-mesenchymal transition and evasion from apoptosis. Therefore, it is essential to thoroughly understand the molecular mechanisms involved in these enzymes in cancerous tissue based on recent literature. Several reviews have highlighted the function of these enzymes in malignancies however the aim of this was to provide more recent overview to their role in malignant transformation and progression and in a briefer approach summarizing the complex molecular pathways. Online databases such as PubMed, Google scholar, Web of Science and MEDLINE were used to identify relevant articles. This approach would assist researchers by providing a list of the potential molecular targets in the sequence of changes related to these enzymes.